ANALISIS PENGKLASIFIKASIAN KUALITAS HADIS DALAM KITAB AL KALIM TAYYIB IBN TAIMIYAH - Ramadhan, Arya (Jurnal Studi Hadis Nusantara, 2023)
Al Kalim Tayyib is a book of Hadith by Ibn Taymiyyah that contains a series ofProphetic traditions about dhikr and prayer. The book, tahqiq by Sheikh MuhammadNashiruddin Al Bani, contains 61 chapters and 253 traditions. The book contains61 chapters and 253 traditions. There are levels of classification of the quality ofthe traditions, namely sahih, hasan, dha'if, and even maudhu'. As a pentahqiq AlBani had a great contribution in perfecting the book of dhikr and prayer (Al KalimTayyib). As stated in his muqaddimah, he has made additions to what is lackingin this book. There are three important points that Al Bani focused on, namelycorrecting the errors in the text, providing important notes on texts that are difficultto understand, and providing information on the quality of the hadith in the text.However, the captioning of the hadith texts in this book has not been done thoroughly. And to find the classification of the quality of the hadith, the researcher conducted further identification using the takhrij method. To practice what is contained in Al Kalim Tayyib, readers can sort out the hadith by referring to this study.